Inventering och riskklassning av förorenade områden i Öna och Östnor - Brömses, Erika (2005)
This work consists of a survey and risk classification of eleven metal industries including foundries, finishers and engineering industries in two industrial areas in Mora. The study follows a method called MIFO (Method of Surveying Contaminated Sites) composed by the Swedish Environmental Protection Agency. In the method assessments of the degree of hazard posed by the pollutants, the level of pollution, the conditions of dispersal, sensitivity and the degree to which the area is worthy to protect are made for each contaminated site (object). The assessment classify the objects into four risk classes in which risk class 1 denotes a very large risk, 2 large risk, 3 moderate risk and risk class 4 little risk. The work of surveying using MIFO is divided into two phases. In the first phase, an over-view of the situation is achieved by studying maps, archives and making visits and interviews. In the second phase, an in-depth study is being done involving sampling of soil water and ground water. The surveying made in this work is mainly a phase 1 study and the investigations were made with help from the County Administrate Board of Dalarna.